Youth and the labour market in Romania - Lincaru, Cristina; Ciucă, Vasilica (ADAPT labour studies book-series., 2014)
In order to improve the quality and efficiency of youth employment, this book examines the cases of the Romanian labour market and of youth employment performance. Recent developments in the labour market participation of young people indicate an accentuation of labour market segmentation and a decrease in job security for young people, with the risk of exclusion and marginalization, fuelled by longer transition processes towards decent employment. This transition may seem clear when one look ...